PERAN BANK SAMPAH DALAM MENINGKATKAN PENDAPATAN MASYARAKAT MELALUI PENGELOLAAN SAMPAH DI DESA RANCAMULYA - Apriansah, Rizki; Firdaus, Nunu Mahmud; Mulyono, Dinno (Comm-Edu (Community Education Journal), 2025)
The Indonesian people are starting to realize the fact that waste is no longer an urgent problem that needs to be avoided, but a solution that must be solved together as an effort to improve the community's economy. Several innovations in waste management are being explored, starting from creating a waste bank as an alternative to raising money to converting organic waste into compost.The purpose of this research is to find out how waste banks can help increase household income in Rancaengang Village, Rancamulya Village. The theory underlying this study is oath management. The research method is a qualitative descriptive research technique that produces written or oral information about the subjects studied and their actions.The results of the study show that the use of waste banks helps reduce waste in the environment and the harmful effects of waste on the environment. Residents of Rancaengang Village can gain economic benefits by utilizing waste management at the waste bank as a job. In conclusion, because waste bank-based waste management increases people's income through waste management, it can be concluded that this has many positive impacts on society. benefits for the economy, the environment, and human health